Effect of Organic (Biochar, Compost and Chicken Manure) and Mineral Fertilization on Available NPK on Sandy Soil - Hassin AL. Makhlof, Hassan Abd El-mawla Mohammeda , Gomoa L. Ahmed (Journal of Pure & Applied Sciences, 2019)
Sandy soils characterize about 90% of the Egyptian soils. Such soils represent a great hope for the agriculture expansion. Soil amendments has been used widely in agriculture lands of Egypt. Thus, two field experiments with design of spit plot were carried out in winter season of 2014-2015 at the Faculty of Agriculture Research Farm, Mansoura University, Egypt  to examine available NPK on sandy soil cultivated by wheat and barley under different application rates of organic and mineral fertilizers. Treatments of organic were chicken manure, compost and biochar, while the studied mineral fertilizer treatments took with rates of  50,75,100 and 125 % .The results showed that available NPK by wheat and barley's soil increased with the application of organic- mineral treatments. The available rate of NPK by wheat's soil were 49.5, 14.5, and382.3 ppm, respectively; while with barley's soil amounted by 57.6, 19.2, and 359.8ppm, were assigned with the treatment of chicken manure + 125% of recommended NPK treatments. The results also revealed that the ability of tested organic-mineral treatments increased the remained available N (85.21%) and P (54.84 %) in barley's soil  and 46.88 and 45% respectively, of wheat's soil compared with 0-0 organic, while available k was higher in wheat's soil than barley. In summary, chicken manure + 125% mineral treatments was the superior in all amendments and gave the highest values of available NPK. Also, Integrated use of organic materials ,and chemical fertilizers is beneficial in improving available N, P and K in soil as well as soil pH and crop yield.